Cryptokey commutation module for secured ip-telephony system - Казимир, В.В.; Риндич, Є.В.; Кенійз, Я.Я. (Proceedings of National Aviation University (archive), 2010)
In the article described programmatic cryptokey switch module for the protected IP – telephony system. Analyzed IP-telephony system’s architecture and determinated the modules place in it. Algorithm of cryptokey switching based on using asymmetric cryptographic transformations for client’s authorization and definition of a secret key for transferring of voice data. Such module’s structure provides secured data transferring channel for users including conferencing.